Корупція в Україні та досвід Польщі: філософсько-політичне підґрунтя проблеми - Владленова, Іліана Вікторівна (Національний юридичний університет ім. Ярослава Мудрого, 2017)
У статті аналізується філософське підґрунтя проблеми корупції. Виводиться, що засади корупції також фундуються в ментальних характеристиках та світоглядних установах, які обумовлено культурою та історією. Досвід поляків, що мають близькі ментальні характеристики з українцями і загальні історичні паралелі, безцінний для України. Хабарництво і корупція мають не тільки економічний, але й моральний аспект. Основне завдання філософії полягає в тому, щоб усунути корупцію шляхом зміни стимулів, настанов, світоглядних орієнтирів. У довгостроковій перспективі стратегії боротьби з корупцією повинні підтримуватися моральним вихованням і зміцненням етичних принципів, що лежать в основі суспільства.

An article the philosophical basis of the problem of corruption analyzed. This shows that the principles of corruption based on mental characteristics and philosophical attitudes conditioned by culture and history. The experience of Poles, who have close psychological characteristics with Ukrainians and common historical parallels, is invaluable for Ukraine. Bribery and corruption have not only an economic but also a moral aspect. The main task of philosophy is to eradicate corruption by changing incentives, stereotypes, ideological guidelines. In the long term, anti-corruption strategies it must be supported by moral education and the strengthening of the ethical principles that underlie society. Despite the difficulties, Ukraine has the potential to overcome corruption. The country rooted problem of corruption, bribery. The problems of corruption and bribery have been rooted in the country since the time of the Soviet Union. Corruption, in turn, causes a crisis of confidence in political power. Ukraine and Poland have a common Soviet heritage. In the Soviet regime, corruption permeated the whole system of society. The experience of the Poles is very important for Ukrainians. Poles have similar mental characteristics. Corruption is the use by government officials and representatives of state bodies of official rights and powers to illegally enriched, receive material and other benefits and benefits both in personal and group interests. The system of corruption is two-sided and works only in the component correlation: the one who gives the reward and the one who receives it. Corruption is a socio-political concept. It includes a set of interrelated problems. It should be noted that the level of corruption in the country is an important marker when choosing a country for investment. The low level of corruption in Poland is one of the reasons why well-known companies choose Poland as a place for doing business. Thus, corruption fits into the system of social relations that people create. Corruption is a product of social reality, so it countered with the help of a social control system. This system maintains a balance of interests. In the situation of modern Ukraine, social control can overcome corruption. It organized as a civil lever of influence and control of its own structures. This is possible only if citizens of Ukraine realize their own responsibility. As part of the fight against corruption in Poland, formed in 2006, the Central Bureau for Combating Corruption. In Poland, corruption is a social and criminal problem, and for corruption, criminal punishment follows. Imperfect institutional structures actually cause or contribute to corruption. Favorable ground for corruption – taxes and duties, government procurement, an institution of officials who distribute subsidies, benefits, medical or educational services, as well as licensing, uneven access to information and the like. Polish researcher А. Surdej notes that corruption thrives where the state perceived as a hostile organization, so people approve of corruption as a way to deceive and undermine the functioning of such a state. In the long term, anti-corruption strategies it must be supported by moral education and ethical principles. Appropriate policies and moral education in the end should solve the problem of corruption. Poland became the first country of the socialist bloc, which launched a peaceful dismantling of the socialist system. She has notable successes. Note that the fight against corruption must be multifaceted, so we must not forget about those mental and ideological institutions that provoke a person to corruption.
Corruption in Ukraine and the experience of Poland: a philosophical and political basis of the problem
Keywords: світоглядні орієнтири; ментальні характеристики; відповідальність; соціальний контроль; corruption; world outlook reference points; mental characteristics; responsibility; social control